Energy-efficient electric motors. - Emadi, Ali, ....- (Boca Raton : CRC, 2005)
This detailed reference provides guidelines for the selection and utilization of electric motors for improved reliability, performance, energy-efficiency, and life-cycle cost. Completely revised and expanded, the book reflects the recent state of the field, as well as recent developments in control electronics, the economics of energy-efficient motors and systems, and advanced power electronic drivers. It includes five new chapters covering key topics such as the fundamentals of power electronics applicable to electric motor drives, adjustable speed drives and their applications, advanced switched reluctance motor drives, and permanent magnet and brushless DC motor drives.
Keywords: Elektrische motoren